THE POTENTIAL OF LOCAL BUSINESS INVOLVEMENT AS A DETERMINANT OF SOCIAL ENTREPRENEURSHIP DEVELOPMENT IN THE PROCESS OF VETERANS' REINTEGRATION - Anna Verbytska; Hanna Dyvnych; Olena Petryk (Baltic Journal of Economic Studies, 2023)
The purpose of the article is to propose an approach to analysing the potential of involving local business as a determinant of social entrepreneurship development in the process of reintegration of veterans. Methodology. The survey is based on the results of an online questionnaire on the current state and needs of business in Chernihiv Oblast in the post-occupation period. The questionnaire contained questions in which respondents could describe business needs, expected support from local governments, and identify favourable and unfavourable factors for the development of the business environment at the regional level. The second part of the empirical research included personal in-depth expert interviews with key informants from business, local government, NGOs and donor initiatives to study the recovery needs of key micro-, small- and medium-sized business sectors in the de-occupied cities of Chernihiv Oblast. The survey results revealed the needs of businesses in the post-occupation period. Despite the fact that the surveyed entrepreneurs note a decrease in income, they are still optimistic about doing business in Chernihiv in the near future. According to the survey, the main factors hindering business development in Chernihiv Oblast are: low solvency of buyers; insufficient financial resources; bureaucratic obstacles; and changes in market conditions. The factors that hinder the development of Chernihiv Oblast are identified: unfavourable conditions for the development of entrepreneurship in the region; lack of external investment in the region; political situation at the local level; unemployment in the region; insufficient level of public initiative and activity of residents. Based on the results of in-depth interviews, it is possible to assess the potential of local businesses in the context of their involvement in the development of social entrepreneurship with a focus on veteran businesses. Despite all the difficulties and problems, the trend towards business recovery in the de-occupation period is positive, based on the desire of entrepreneurs to work in the Chernihiv Oblast. The city has active and influential NGOs that are ready to act in the interests of the community. Currently, donor initiatives in the region are just beginning. Practical implications. Based on a study of the reintegration needs and problems of servicemen, veterans and their family members in starting their own business and an analysis of the local business environment, recommendations are made on the role of business in the development of social entrepreneurship of veterans as a tool for their reintegration. Value/originality. The research demonstrates an approach to determining the potential of business in its involvement in the development of social entrepreneurship as a tool for reintegrating veterans at the local level.